Written on the wind [large type] - Camden, Elizabeth, 1965- (Camden, Elizabeth, 1965- Blackstone legacy, 2022)
"He carries a dangerous secret, but can he survive long enough to expose it? Count Dimitri Sokolov has been charged with overseeing construction of the legendary Trans-Siberian Railway, but during this work, he witnesses an appalling crime, the truth of which threatens the Russian monarchy. In an effort to silence him, the czar has stripped Dimitri of his title, his lands, and his freedom . . . but Dimitri has one asset the czar knows nothing about: his deep and abiding friendship with Natalia Blackstone. Natalia is the lead analyst for her father's New York banking empire and manages their investment in the Trans-Siberian Railway. Her bond with Dimitri has flourished despite the miles between them, but when Dimitri goes unexpectedly missing, she sets the wheels in motion to find him. Once they join forces, they embark on a dangerous quest in which one wrong move could destroy them both. From the steppes of Russia to the corridors of power in Washington, Dimitri and Natalia will fight against all odds to save the railroad while exposing the truth. Can their newfound love survive the ordeal?"--